Foreword to the special section on recent advances in graphics and interaction - Rodrigues, Nuno (2022)
This special section on Recent Advances in Graphics and In- teraction features the papers submitted to Computers & Graphics (C&G) and presented at the 2021 edition of the International Conference on Graphics and Interaction – ICGI’2021 – which was held on November 4 and 5, 2021 at the Faculty of Engineering of the University of Porto, Portugal, as a joint organization with the Eurographics Portuguese Chapter — GPCG.